Digital competence and the use of technological resources by teachers in music conservatories and schools of music (Música Hodie, 2021)
At present, digital technology provides innumerable new possibilities in the field of musical education. Its tools are, without a doubt, a valuable mediator in teaching-learning processes at the levels of elementary and university education, and specialisation. This study examines the knowledge and use of technological resources in the specific sphere of teaching in elementary, intermediate and superior stages in music conservatories and schools of music. By means of an online questionnaire administered to 82 teachers in this field, significant data was obtained regarding said knowledge and use of technological tools. These results provide evidence that those tools are scarcely applied, whether in preparing classes or in learning processes in the classroom. The only positive data appears in connection with the use of sound and sheet music editors.